The Influence of Gadget Use on Early Childhood Social Interaction - Eliana, Lina; yanti, Sefri; Oktaviana, Anita (JUPE : Jurnal Pendidikan Mandala, 2025)
Technological advances that are increasingly developing are a necessity that cannot be denied. The development of this technology can help children in finding various kinds of information. However, behind the advantages of gadgets, there are also negative effects caused by gadgets such as the lack of children in socializing and interacting with their peers. This study aims to determine whether there is an influence on children between before and after using gadgets on their social interactions. The method that the researcher uses is a quantitative method using data in the form of numbers, the data in this study were obtained through questionnaires and observations, then the researchers conducted an analysis, the first thing the researchers did was a prerequisite test in the form of a normality test and a homogeneity test. The next step taken by the researcher was to analyze the data using the t-test technique with the help of SPSS Windows Ver. 25. Based on the results obtained in this study, there is a significant influence on early childhood social interactions between before and after using gadgets. These results can be seen from the comparative analysis in the paired sample test table which shows that the calculated alpha = 0.000 and the alpha test = 0.05, so that the calculated alpha < test alpha.